Sanctions for Intimate Partner Sexual Violence: Is the Law on the Books the Law in Action? - Bielen, Samantha (Journal of interpersonal violence, 2022)
Intimate partner sexual violence (IPSV) is common, yet in many jurisdictions the law still does not adequately recognize it. In those jurisdictions that have formally criminalized IPSV, little is known about the extent to which IPSV-related law on the books is implemented in practice. Especially scarce is systematic quantitative evidence on the processing of IPSV cases by the justice system. We investigate unique case-level court data on the processing and sanctioning of violent sex crime cases in Belgium, a jurisdiction where the law adequately criminalizes IPSV, but where criminal judges are afforded broad sentencing discretion. Our data allow us to observe both the conviction and the sentencing decision. Consequently, we are able to address the endogenous sample selection concerns that arise in the assessment of IPSV-related sentencing disparities by estimating a full-fledged sample selection model. Upon inclusion of a broad range of defendant, victim, and other case controls, we show that defendants who are the victims? spouses or partners receive statistically significantly shorter prison sentences than defendants who are unrelated to the victims, in the sense that they are neither the victims? current or former spouses nor family. The documented extralegal disparity is quantitatively noteworthy and survives a series of robustness checks as well as alternative model specifications. Our analysis thus lends empirical credibility to the perspective that while national legislatures have often been slow to address IPSV, the justice systems may be even slower at internalizing the corresponding law. Our evidence-based insight into de facto legal responses to IPSV is of direct relevance to many jurisdictions globally.